Ultrasound-Assisted Preparation of Exopolysaccharide/Nystatin Nanoemulsion for Treatment of Vulvovaginal Candidiasis - Song R (Dove Medical Press, 2020)
Ruiteng Song,1 Fang Yan,1 Min Cheng,2 Fakun Dong,1 Yongqi Lin,1 Yuzhen Wang,3 Bo Song1 1School of Pharmacy, Weifang Medical University, Weifang, Shandong 261053, People’s Republic of China; 2Clinical Medical College, Weifang Medical University, Weifang, Shandong 261053, People’s Republic of China; 3Medical Imaging Specialty, Weifang Medical University, Weifang, Shandong 261053, People’s Republic of ChinaCorrespondence: Yuzhen Wang; Bo SongWeifang Medical University, Baotong Street, No. 7166, Weifang, Shandong 261053, People’s Republic of ChinaTel +86-536-8462490Email wangyz@wfmc.edu.cn; songsbob@163.comPurpose: As one of the classic anti-Canidia albicans (CA) and vulvovaginal candidiasis (VVC) drugs, nystatin (NYS) is limited by poor water solubility and easy aggregation. Traditional NYS vaginal delivery formulations do not fully adapt to the specific environment of the vaginal cavity. The use of exopolysaccharides (EPS) has great application potential in emulsifiers, but its use has not been reported in nanoemulsions. In this work, an EPS/NYS nanoemulsion (ENNE) was developed to improve the activities of NYS against CA and VVCMethods: The ENNE was prepared by ultrasonic method using EPS as an emulsifier, liquid paraffin oil as an oil phase, PEG400 as a co-emulsifier, and NYS as the loaded drug. ENNE preparation was optimized by response surface method. After optimization, in vitro and in vivo analysis of the anti-CA activity; animal experiments; staining with propidium iodide (PI), periodic acid-schiff (PAS), and hematoxylin-eosin (H&E); and cytokine experiments were performed to investigate the therapeutic ability against VVC.Results: The optimal formulation and preparation parameters of ENNE were determined as follows: EPS content of 1.5%, PEG400 content of 3.2%, NYS content of 700 μg/mL, paraffin oil content of 5.0%, ultrasonic time of 15 min, and ultrasonic amplitude of 35%. The ENNE showed an encapsulated structure with an average particle size of 131.1 ± 4.32 nm. ENNE exhibited high storage and pH stability, as well as slow release. The minimum inhibitory concentration (MIC) of ENNE against CA was only 0.125 μg/mL and the inhibition zone was 19.0 ± 0.5 mm, for greatly improved anti-CA effect. The prepared ENNE destroyed the membrane of CA cells, and exhibited good anti-CA effect in vivo and therapeutic ability against VVC.Conclusion: The results of this study will promote the application of EPS in nanotechnology, which should lead to new and effective local drug formulations for treating VVC.Keywords: Canidia albicans, ultrasonic, response surface method, antifungal